Implementation of radiochromic film dosimetry protocol for volumetric dose assessments to various organs during diagnostic CT procedures - Brady, Samuel (American Association of Physicists in Medicine, 2010)
Purpose: The authors present a means to measure high-resolution, two-dimensional organ dose distributions in an anthropomorphic phantom of heterogeneous tissue composition using XRQA radiochromic film. Dose distributions are presented for the lungs, liver, and kidneys to demonstrate the organ volume dosimetry technique. XRQA film response accuracy was validated using thermoluminescent dosimeters (TLDs). Methods: XRQA film and TLDs were first exposed at the center of two CTDI head phantoms placed end-to-end, allowing for a simple cylindrical phantom of uniform scatter material for verification of film response accuracy and sensitivity in a computed tomography (CT) exposure geometry; the TLD and film dosimeters were exposed separately. In a similar manner, TLDs and films were placed between cross-sectional slabs of a 5 yr old anthropomorphic phantom’s thorax and abdomen regions. The anthropomorphic phantom was used to emulate real pediatric patient geometry and scatter conditions. The phantom consisted of five different tissue types manufactured to attenuate the x-ray beam within 1%–3% of normal tissues at CT beam energies. Software was written to individually calibrate TLD and film dosimeter responses for different tissue attenuation factors, to spatially register dosimeters, and to extract dose responses from film for TLD comparison. TLDs were compared to film regions of interest extracted at spatial locations corresponding to the TLD locations. Results: For the CTDI phantom exposure, the film and TLDs measured an average difference in dose response of 45% (SD±2%). Similar comparisons within the anthropomorphic phantom also indicated a consistent difference, tracking along the low and high dose regions, for the lung (28%) (SD±8%) and liver and kidneys (15%) (SD±4%). The difference between the measured film and TLD dose values was due to the lower response sensitivity of the film that arose when the film was oriented with its large surface area parallel to the main axis of the CT beam. The consistency in dose response difference allowed for a tissue specific correction to be applied. Once corrected, the average film response agreed to better than 3% (SD±2%) for the CTDI scans, and for the anthropomorphic phantom scans: 3% (SD±3%) for the lungs, 5% (SD±3%) for the liver, and 4% (SD±3%) for the kidneys. Additionally, XRQA film measured a heterogeneous dose distribution within the organ volumes. The extent of the dose distribution heterogeneity was not measurable with the TLDs due to the limitation on the number of TLDs loadable in the regions of the phantom organs. In this regard, XRQA film demonstrated an advantage over the TLD method by discovering a 15% greater maximum dose to lung in a region unmeasured by TLDs. Conclusions: The films demonstrated a lower sensitivity to absorbed dose measurements due to the geometric inefficiency of measuring dose from a beam situated end-on to the film. Once corrected, the film demonstrated equivalent dose measurement accuracy as TLD detectors with the added advantage of relatively simple measurement of high-resolution dose distributions throughout organ volumes.